Viral di Tiktok Tapi Berujung Bangkrut:Mengapa Usaha Mikro Wajib Punya Analisis Kelayakan Finansial - Ghiska Mayalnie; Zahra Maylani; Sutantri Sutantri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the phenomenon of micro-enterprises that gain widespread popularity through TikTok but eventually go bankrupt due to weak financial management. Viral exposure on social media often triggers a sudden surge in consumer demand, creating the perception of business success. However, this rapid increase in demand is not always supported by sufficient capital, effective cash flow management, adequate production capacity, or proper cost planning. As a result, many business owners struggle to meet market demand, maintain operational stability, and sustain long-term business performance. This study emphasizes the importance of financial feasibility analysis as a fundamental basis for decision-making before establishing or expanding a business. The analysis includes profit and loss projections, cash flow analysis, break-even point calculations, working capital requirements, and the identification of potential financial risks. The findings indicate that popularity on social media alone cannot guarantee business success unless it is accompanied by sound financial planning and management. Therefore, micro-enterprise owners should implement comprehensive financial feasibility analyses to support healthy business growth, improve profitability, and ensure long-term sustainability in an increasingly competitive and rapidly evolving digital marketplace.